Did they stay or did they go? : a follow-up study of youth migration intentions and behaviors in the Northern Westfjords of Iceland - Kelly, Erin Diane, 1995- (2021)
In this paper, migration intentions among adolescents are explored in the setting of remote fishing villages in the Westfjords of Iceland, and how perceptions of job opportunities and gender roles in their home communities influence these intentions. This research is a follow-up study to Bjarnason and Thorlindsson (2006) who surveyed teenagers on their migration and career aspirations, by following up with the same cohort who are now in their early 30s through semi-structured interviews on their decision-making process to stay, leave or move out of and eventually return to their home communities. Using the Theory of Planned Behavior (Ajzen 1991), these processes are analyzed to determine how their perceptions and intentions influenced migration behaviors over time. It is found that each decision-making process, although unique to the individual, generally comes from a place of agency and free will for each to decide their migration behaviors on their own volition and without any external force. Those who stayed were content to do so, those who left did so in search of a different lifestyle, and some who left ended up returning at a later period of time. However, some anecdotal evidence shows that gender disparities that exist working in local fisheries, one of the region’s primary industries, can possibly be a factor in female out-migration levels. Youth migration in this region of the country has been prevalent over the years as local adolescents in these fishing communities migrate to more urban areas in pursuit of higher education or better job opportunities, but this trend has recently been in decline (Garðarsdóttir, Bjarnason, Jónsson, & Shuttleworth, 2020). In conclusion, the limitations of this research call for a broader and more quantitative analysis to further determine these patterns, and also an examination of how the presence of international immigrants in these communities has an impact on these migration behaviors. Í þessari ritgerð er tilhneiging ungs fólks í sjávarbyggðum Vestfjarða til ...